1994
DOI: 10.1136/adc.70.5.395
|View full text |Cite
|
Sign up to set email alerts
|

Family history and recurrence of febrile seizures.

Abstract: To determine the value of a detailed family history for the assessment of the risk of recurrence of febrile seizures, 115 children who visited the emergency room of an academic children's hospital were studied prospectively. Moreover, it is still not possible to discriminate between children who will and children who will not have a recurrence. Further improvements in the ability to predict the recurrence of a febrile seizure will aid doctors in choosing the appropriate prophylactic treatment, if any.A first d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 24 publications
2
22
0
3
Order By: Relevance
“…Furthermore, although both daily phenobarbitone and diazepam with fever have been shown to reduce the chances of recurrent FC [14, 17, 41], studies have not demonstrated reduction in subsequent epilepsy [17, 35, 42, 43]. Moreover, prolonged prophylactic treatment has adverse effects [44, 45, 46, 47, 48]. Some authorities advise AEDs for FCs only for ‘frequent recurrences’ [49, 50], if prolonged FCs (over 20 min) occur before age 9 months or after a third FC [51], and others advise them for complex features or in children with neurological deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although both daily phenobarbitone and diazepam with fever have been shown to reduce the chances of recurrent FC [14, 17, 41], studies have not demonstrated reduction in subsequent epilepsy [17, 35, 42, 43]. Moreover, prolonged prophylactic treatment has adverse effects [44, 45, 46, 47, 48]. Some authorities advise AEDs for FCs only for ‘frequent recurrences’ [49, 50], if prolonged FCs (over 20 min) occur before age 9 months or after a third FC [51], and others advise them for complex features or in children with neurological deficit.…”
Section: Discussionmentioning
confidence: 99%
“…About 20% of families had two or more affected relatives and the scores tended to capture this information. It is worth noting that the formulation of Van Esch et al [1994], simply the proportion of relatives affected, without regard to age or sex, adequately described these data.…”
Section: Discussionmentioning
confidence: 99%
“…FHS-1, adjusting for family size, improved the fit better than Schwartz et al [1988], the formulations being otherwise identical. The Chakraborty et al [1984] 0.47 0.49 Williams et al [1984] 7.99 0.005 Fain and Goldgar [1986] 4.87 0.03 Lynch et al [1986] 3.97 0.05 Reed et al [1986] 9.32 0.002 Schwartz et al (b) [1988] 0.63 0.43 Groeneveld and Hitzeroth [1991] 9.69 0.002 Kee et al [1991] 0.49 0.48 Van Esch et al (a) [1994] 10.00 0.002 Kerber (a) [1995] 11.54 0.001 Kerber (b) [1995] 11.30 0.001 Kerber (c) [1995] 2.77 0.10 FHS-1 6.01 0.01 FHS-2 11.61 0.001 *One or more first-degree relatives affected before 60 years of age.…”
Section: Fitting Scores To Chd Case/control Datamentioning
confidence: 99%
See 1 more Smart Citation
“…12,37 Van Esch ve ark., 1. derece akrabalarında FK öyküsü olan çocuklarda, rekürrens riskini %52 olarak bulmuşlardır. 38 Berg ve ark. ise 1.derece akrabalarda FK öyküsü olanlarda rekürrens riskini %45.5, olmayanlarda ise %26,3 olarak belirtmişler-dir.…”
Section: Discussionunclassified